Tl-Ba-Ca-Cu-O thin films on buffered substrates for microwave device applications - Bramley, A; Glassey, B; Grovenor, C; Goringe, M (1997)
Tl-Ba-Ca-Cu-O thin films have been grown on a variety of substrates, both with and without the use of buffer layers. Differences in processing routes required for the various film-substrate combinations are highlighted and the effect of the buffering layers on the microstructure, transport and microwave properties of the films are discussed. © 1997 IEEE.